Determinants of financial sustainability for microfinance institutions: lessons for Islamic microfinance banks in Nigeria - Abdullahi, Abdurrahman; Othman, Anwar Hasan Abdullah (2020)
Islamic microfinance institutions play a major role in the provision of financial services to the poor and underprivileged through non-interest, equity-based products and services. To achieve these critical objectives, however, they need to be financially sustainable, which is threatened by the current economic and financial crisis caused by the Covid-19 pandemic. The objective of this paper is to review the determinants of financial sustainability of microfinance institutions with a view to draw lessons for Islamic microfinance banks in Nigeria. The paper utilized the literature review methodology to synthesize research finding in the area. The review revealed that the major determinants of financial sustainability of microfinance institutions are capital structure, asset size and financial innovation. Others are good risk management and corporate governance frameworks. The paper thus recommended that Islamic microfinance institutions in Nigeria should maintain a robust capital structure that relies more on equity, a lean but diversified Board, and utilize more technology-based services. Most importantly, they should emphasize profit and loss sharing principles in their operations.